Pro-inflammatory and anti-inflammatory cytokines in neonates during the acute period of novel coronavirus infection - E. V. Moskaleva; A. G. Petrova; L. V. Rychkova; L. F. Sholokhov; M. R. Akhmedzyanova; N. V. Semenova; E. A. Novikova; A. A. Kharkhorina; L. I. Kolesnikova (Acta Biomedica Scientifica, 2024)
Background. Research results on the immune response and cytokine profile in children with the new coronavirus infection SARS-CoV-2 are contradictory and insufficient, which necessitates the need to understand the nature of the course of the disease depending on age and severity of the infection. The importance of assessing risks and predicting the consequences of a new coronavirus infection in childhood makes the study of serum concentrations of pro-inflammatory and anti-inflammatory cytokines relevant.The aim. To study the level of pro-inflammatory and anti-inflammatory cytokines in newborns during the acute period of a new coronavirus infection to determine the characteristics of the immune response and identify prognostic criteria for the course of the infectious process.Materials and methods. The article presents the results of a study of the level of pro-inflammatory, anti-inflammatory cytokines and C-reactive protein (CRP) in newborns (n  =  44) hospitalized with a confirmed new coronavirus infection of varying severity. The study was conducted during the acute period of COVID-19.Results. Cytokine concentrations in the blood serum of newborns were determined by enzyme immunoassay. In newborns in the acute period of a new coronavirus infection, regardless of the severity, there is a decrease in serum concentrations of interleukin-1β, interleukin-4, interleukin-6, interleukin-8, tumor necrosis factor α, interferon (INF)  γ and  CRP compared with the control group. The level of INF-α in the blood serum of newborns of both the main and control groups did not have significant differences.Conclusions. The cytokine profile in newborns with the new coronavirus infection SARS-CoV-2 may be due to inhibition of the innate immune system, which requires further research in this direction and increased pediatric attention to this category of children.